Linear Programming Optimization of Nutrient Addition on Biogas Waste and Goat Compost as Granules Fertilizer Raw Materials - Argo, Bambang Dwi; Lutfi, Musthofa; Suherman, Suherman (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
The objective of this study was to determine the optimum values of nutrient (i.e. nitrogen, phosphorus, potassium) added from inorganic fertilizers (i.e. KNO3, SP-36, Urea) to some alternatives raw materials of organic fertilizer using linear programming. Some alternatives raw materials of organic fertilizer in this study were biogas waste (Formula I) and goat compost (Formula II). The content of total N, C-organic, organic matter content of P2O5, K2O and Cation exchangeable capacity (CEC) were analyzed as parameters. The results indicate that the formula II with goat compost as raw materials was the best formula which has the average nutrient element close to the national standard of organic fertilizers with 23.16% of C-organic, 2.20% of N, 2.19% of P2O5 and 0.69% of K2O. In addition, the production cost of organic fertilizer base on formula II was cheaper than other formula i.e. IDR 1.15/g. Keywords: organic fertilizer, optimization, linear programming